2021
DOI: 10.3390/pr9091565
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Methane Potential of Energy Crops: An Overview on Types of Data Sources and Their Limitations

Abstract: As the anaerobic digestion of energy crops and crop residues becomes more widely applied for bioenergy production, planners and operators of biogas plants, and farmers who consider growing such crops, have a need for information on potential biogas and methane yields. A rich body of literature reports methane yields for a variety of such materials. These data have been obtained with different testing methods. This work elaborates an overview on the types of data source available and the methods that are common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 114 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…Previously reported biomethane potential values for grasses vary considerably: 222 mL CH 4 /g VS [3], 261 mL CH 4 /g VS [52], 285 mL CH 4 /g VS [15], 292 mL CH 4 /g VS [9], 308-340 mL CH 4 /g VS [13], 327 mL CH 4 /g VS [14], 341-493 mL CH 4 /g VS [53], 400 mL CH 4 /g VS [5] and 403 mL CH 4 /g VS [16]. The variation in biomethane potential values is likely due to a combination of factors, including biochemical composition, plant maturity [6], interspecies variation [54], harvest season [13] and differences between the methodologies used to determine biomethane potential [53,55]. The E BMP results of the grass used in this study correspond with those previously reported for grass silage [52] and grasses collected from a University campus [15] and sports fields [9].…”
Section: Biomethane Potential Of Hydrothermal Productsmentioning
confidence: 99%
“…Previously reported biomethane potential values for grasses vary considerably: 222 mL CH 4 /g VS [3], 261 mL CH 4 /g VS [52], 285 mL CH 4 /g VS [15], 292 mL CH 4 /g VS [9], 308-340 mL CH 4 /g VS [13], 327 mL CH 4 /g VS [14], 341-493 mL CH 4 /g VS [53], 400 mL CH 4 /g VS [5] and 403 mL CH 4 /g VS [16]. The variation in biomethane potential values is likely due to a combination of factors, including biochemical composition, plant maturity [6], interspecies variation [54], harvest season [13] and differences between the methodologies used to determine biomethane potential [53,55]. The E BMP results of the grass used in this study correspond with those previously reported for grass silage [52] and grasses collected from a University campus [15] and sports fields [9].…”
Section: Biomethane Potential Of Hydrothermal Productsmentioning
confidence: 99%
“…The AD technology Cc was determined using a compilation of the biomethane potential (BMP) values reported for different feedstocks and process conditions. BMP is defined as the specific methane production from a given substrate under specific digestion conditions [20]. Details on these calculations are in the supporting database.…”
Section: đ”đ”đ”đ”đ”đ” * đ”đ”đ”đ”đ”đ” đ”đ”đ”đ”đ”đ”mentioning
confidence: 99%
“…One way to reduce these impacts is to grow crops in protected environments but this is not always possible. Crops that require large expanses of land or acreage of land, such as soybeans, wheat and corn, are examples of this [4,5]. However other crops, such as horticultural crops, and mushrooms are amenable to cultivation in protected environments.…”
Section: Introductionmentioning
confidence: 99%